An examination of nationwide trends in accelerated partial breast irradiation – The replacement of breast brachytherapy with intraoperative radiotherapy and external beam radiation. (January 2022) - Ladbury, Colton; Liu, Jason; Radany, Eric; Vora, Nayana; Amini, Arya; Beriwal, Sushil; Yashar, Catheryn; Shah, Chirag; Glaser, Scott
Highlights: APBI use is stable since 2008, but with a drop in brachytherapy and a rise in IORT. There is a steady rise in patients considered "suitable" by ASTRO APBI guidelines. Trends in APBI modality utilization appears to be influenced by available literature. Abstract: Purpose: To examine recent modality utilization trends in accelerated partial breast irradiation (APBI) in the National Cancer Database (NCDB) based on the American Society for Radiation Oncology (ASTRO) guidelines. Materials and Methods: A total of 58, 194 patients treated with APBI were identified. Patients were segregated by APBI modality (brachytherapy, external beam radiotherapy [EBRT], and intraoperative radiotherapy ([IORT]). These patients were then further classified by suitability to receive APBI based on ASTRO guidelines. Temporal trends in utilization were evaluated using linear regression. Logistic regression was applied to study factors contributing to APBI modality choice and treatment within the ASTRO suitability groups. Results: Patients treated with brachytherapy, EBRT, and IORT comprised 70.5%, 17.5%, and 12.0% of patients treated with APBI. From 2008 to 2017, total APBI cases remained relatively stable (−54.1 cases/year, p  = 0.161) while brachytherapy cases decreased by 258.7 cases/year ( p  < 0.001). EBRT and IORT increased by 51.5 cases/year ( p  = 0.019) and 153.1 cases/year ( p  < 0.001), respectively. 40.0% of patients treated with APBI were classified as "suitable", which increased from 2010 to 2017 from 35.3% to 45.3% (slope = 1.51%/year, r 2  = 0.61, p  = 0.022). In comparison, 36.0% (36.1% in 2010 to 33.1% in 2017) of patients were classified as "cautionary" (slope = −0.33%/year, r 2  = 0.63, p  = 0.019) and 23.9% (28.6% in 2010 to 21.6% in 2017) of patients were classified as "unsuitable" (slope = −1.18%/year, r 2  = 0.67, p  = 0.012). Conclusions: While overall APBI utilization has remained stable since 2008, this has been accompanied by a decline in brachytherapy and a rise in IORT. The causes of these trends should be the topic of future research.